The Effectiveness of Developing the ‘Deep Talk’ Flash Card Media in Group Guidance Services to Improve Further Study Planning for Ninth-Grade Students of SMP N 1 Dukuhwaru - Arini Himawati; Hanung Sudibyo; Rahmad Agung Nugroho (MASI Mandiri Edukasi, 2025)
This study aims to develop the “Deep Talk” Flash Card media as an innovative tool in group guidance services to enhance junior high school students’ ability to plan their future studies. The research was motivated by the fact that many ninth-grade students still experience confusion about their next educational pathway due to limited self-reflection skills, insufficient career information, and a lack of interactive counselling media. This study employed a Research and Development (R&D) approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The research subjects consisted of 20 ninth-grade students from SMP Negeri 1 Dukuhwaru, and the media’s feasibility was assessed by a material expert and a media expert. Data were collected through needs assessment questionnaires, validation sheets, pre-test and post-test instruments, and observation guidelines. The results show that the Deep Talk Flash Card media was categorised as highly feasible, with feasibility scores of 89% for the material aspect and 92% for the media aspect. The implementation of group guidance using this media effectively improved students’ study planning abilities, as indicated by an increase from the “fair” category in the pre-test to the “good” category in the post-test. Students also demonstrated greater engagement, higher confidence in expressing opinions, and improved reflective skills. Thus, the Deep Talk Flash Card media is effective and can serve as an innovative alternative for school counsellors to help students make more mature, well-directed educational decisions.